Shaker table design for electronic device vibration test system - Siswanto, Waluyo Adi; Ibrahim, Mohd Norihan; Madlan, Mohd Amran; Mohamad, Siti Mariah (IJET, 2011)
A general purpose vibration test system has been developed to provide a testing platform for electronic devices. This paper presents the design of the shaker table for the platform-testing base where an electronic device will be placed and excited by the vibration exciter. Three design models are first analyzed their natural frequencies and the corresponding mode shapes. The model with the lightest weight and the highest first natural frequency is then selected to be manufactured. This selected shaker stable can be used in a frequency range of service up to 2500 Hz and behaves as a rigid body when it vibrates. The maximum dimension of the electronic device that can be placed in the shaker table is 15 cm square. This paper also provides the general frequency range limitation when the vibration test is used at constant displacement or constant acceleration test. The suggested frequency ranges satisfy all limitation requirements of the shaker.